Paths to the Assembly in British North America:: New Brunswick, 1786-1837 - Klein, Kim (Acadiensis, 2010)
Abstract During the late 18th and early 19th centuries, New Brunswick assemblymen followed paths to the assembly that conformed to colonial British American standards. These paths included securing appointments to important local offices and accumulating wealth and economic influence. Because many first-generation assemblymen successfully transferred these assets to their political heirs, prominent social origins and the family connections that accompanied them had become important components of electoral success by the time that the colony’s second generation of elected political leaders entered the assembly during the 1810s and 1820s. This development signified the emergence of local oligarchies in numerous New Brunswick constituencies.